The Already Dead : The New Time of Politics, Culture, and Illness - Cazdyn, Eric M. (Book collections on Project MUSE., 2012)
This book considers how a culture of crisis management-what Cazdyn calls ""the new chronic""--Has come to dominate all aspects of contemporary life, from biomedicine to economics to politics. Drawing from his own experiences battling leukemia and the subsequent effects of his illness on the process of becoming a Canadian citizen, Cazdyn unravels the logic of the new chronic where people find themselves suspended in a space between life and death